Analysis and management of GNSS reference station data - Gülal, Vahap Engin; Dindar, Ahmet Anıl; Akpınar, Burak; Tiryakioğlu, İbrahim; Aykut, Nedim Onur; Erdoğan, Hediye (Univ Osijek, Tech Fac, Trg Ivane Brlic-Mazuranic 2, Slavonski Brod, Hr-35000, Croatia, 2015)
Global Navigation and Satellite System (GNSS) is used in a wide range of applications from low accuracy navigation to high accuracy point positioning. GNSS reference stations are required for using the GNSS applications effectively. GNSS reference stations at the Yildiz Technical University in IstanbulTurkey (YLDZ) and at the Afyon Kocatepe University in Afyon-Turkey (AFKU) were established within the scope of the research projects supported by their universities in 2013. In this study, quality control procedure, data process, analysis and management of YLDZ reference station data are explained. Besides, test results about the Real Time Kinematic (RTK) positioning method of the reference station are given. The reference station YLDZ meets the International GNSS Service (IGS) standards based on the processing results. According to the RTK results, coordinates can be determined with 1,5 cm and better accuracy on the field by using YLDZ station.
Keywords: Analysis of time series; GNSS; GNSS data management; Reference station; RTK positioning; Time-Series; Outliers; Turkey; Displacements; Velocity